PENERAPAN HASIL BELAJAR LONGTORSO PADA PEMBUATAN POLA WEDDING GOWN - Rani Puspa Sari; Astuti Astuti (Fesyen Perspektif, 2015)
This research examined the application of longtorso learning result in making wedding gown pattern, which is done in LPK Quenta Busana in force learners 2012/2013 and 2013/2014 linseri advanced level. This research aimed to gain an overview or learning result data  longtorso learning result in terms of characteristics, ideology images, model analysis, how to measure, and burst pattern on wedding gown pattern making. The method used is descriptive method. The sample used is total sample amount to 32 person. The data collecting instruments of this present research were questionnaires . The conclusion of this research indicated that  the application of the learning result in terms of the characteristics longtorso, ideology images, model analysis, how to measure, and burst pattern on pattern making wedding gown, more than half of the learners have the ability to apply the results of the study and only a small percentage that have not applied it. Suggestion that submitted  is the learners in order to develop and enhance the skills and ability to understand how to practice drawing, analyze, measure, and make a pattern on wedding gown pattern making.